Deferred tax and earnings management under MASB 25 / Noor Hasimah M. Yacob, Nor'Azam Mastuki and Rohaya Md Noor - M. Yacob, Hasimah; Mastuki, Nor'azam; Md Noor, Rohaya (Research Management Institute (RMI), 2011)
This paper investigates whether Malaysian publicly listed companies in 10 sectors use deferred tax and discretionary accruals as tools to manage earnings in order to meet earning targets: 1) to avoid an earning decline and 2) to avoid a loss. This research examines financial statements prepared during the period 2003 to 2005 when the Malaysian Accounting Standard Board (MASB) 25 Accounting for Income Taxes was in place. This study uses Burgstahler and Dichev's approach to identify earnings management firms. Healy's model and a modified Jones model are also employed to identify and separate accruals. The results show no evidence that deferred tax has been used by firms as a tool to manage earnings during the period of study. The finding suggests that the implementation of the MASB 25 (now known as Financial Reporting Standard (FRS) 112), which is more comprehensive and specific than lAS 12, has reduced the use of deferred tax by firms in managing their earnings. In contrast, the findings of this study provide evidence that firms use discretionary accruals to avoid reporting losses. The results ofthis study may be of use to researchers studying earnings management behavior and for standard setters with regard to establishing and monitoring standards.